THE MILITARY SERVICE AS PART OF THE SOCIAL IDEAL IN SERBIA - Starčević, Srđan (Serbian political thought, 2023)
Compulsory conscriptionin Serbia was established in the 19th century, and the military as a social institutionrapidly became an indispensable part of the socialization processof citizens. It remained so until 2011, which lent credibility to the strategic considerations of deterrence and total defense of that time. The return of war to European soil actualizes the issue of society’s readiness for defense in many European countries. Serbian society has changed significantly in the two previous decades, becoming largely described by Bauman’s fluid modernity, and the capacity of citizens for armed and unarmed resistance in the event of war has significantly declined. Starting from the assumption that the suspension of the compulsory conscription remains valid, the authors examine the possibilities for increasing the interest of young people in voluntary military service, which is the subject of this paper. The aim of the paper is to show the necessity, justification and content of state incentives for young people who opt for military service, as well as to point out their probable social consequences. The theoretical framework of the work is the theory of the network society of Manuel Castells and his understanding of individuation as a cultural tendency of modern society that differs from individualism. The authors conclude that increasing interest in voluntary military service is possible by connecting individual projects of citizens with military service as part of a common, social ideal in Serbia.State incentives for voluntary military service and, subsequently, participation in the active and passive reserves, could be divided into three groups. The first would be incentives related to employment, the second would be cooperation between the state and civic initiatives and organizations, and the third would be incentives related to business and tax incentives.